2011
DOI: 10.1118/1.3622605
|View full text |Cite
|
Sign up to set email alerts
|

The influence of field strength and different clinical breast MRI protocols on the outcome of texture analysis using foam phantoms

Abstract: This phantom study shows that acquisition parameters and protocols that are typically used for clinical breast imaging can result in good TA. Our findings suggest that changes to sequence parameters may not greatly influence the outcome of texture analysis, but rather that spatial resolution may be the most important factor to consider.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 35 publications
2
58
0
Order By: Relevance
“…Although data was acquired under two different imaging conditions, which may introduce an additional variable, it has been previously reported that robust texture analysis can be performed across different magnets and clinical protocols, providing the spatial resolution remains constant, as it does in this study [23,38,39].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Although data was acquired under two different imaging conditions, which may introduce an additional variable, it has been previously reported that robust texture analysis can be performed across different magnets and clinical protocols, providing the spatial resolution remains constant, as it does in this study [23,38,39].…”
Section: Discussionmentioning
confidence: 94%
“…Image data was re-binned to 6 bits/pixel according to previous experience, the literature, and recommendations from the software developers [22,23]. Grey-level normalisation, which is known to minimise the effect of brightness and contrast variations on the outcome of TA [24,25], was carried out within MaZda by rescaling the histogram data to fit within μ± 3σ (μ-grey-level mean, σ-grey-level standard deviation).…”
Section: Texture Analysismentioning
confidence: 99%
“…The influence of the acquisition protocol on textural measures has been controversial in the literature and may depend on the specific parameter, tumors studied, etc [13, 14, 15, 16, 17]. Mayerhoefer et al [13] and Waugh et al [14] studied the influence of different clinical breast MRI protocols and parameters on the results of several textural features.…”
Section: Introductionmentioning
confidence: 99%
“…Mayerhoefer et al [13] and Waugh et al [14] studied the influence of different clinical breast MRI protocols and parameters on the results of several textural features. They showed that spatial resolution is the most important factor influencing textural measures, while changes to other protocol parameters did not change the outcome of texture analyses so significantly.…”
Section: Introductionmentioning
confidence: 99%
“…Although slightly different MRI protocols were used (1.5 T and 3 T), it is well known that changes to MRI sequence parameters are less critical for the outcome of texture analysis than spatial resolution, which may be the most important factor to consider. 17,18 In this work, we selected a set of classical textural features of local (CM) and regional (RLM) nature. Histograms are also classical tools for heterogeneity computation.…”
Section: Correlationsmentioning
confidence: 99%